Evaluation of Preparedness and Recovery Needs of Private Well Users After the Great Louisiana Flood of 2016. Issue 6 (November 2021) - Gilliland, Aubrey E.; Pieper, Kelsey J.; Straif-Bourgeois, Susanne; Rhoads, William J.; Dai, Dongjuan; Edwards, Marc; Brisolara, Kari; Olexia, Darcie; Katner, Adrienne
Abstract : Context: The August 2016 Louisiana flood marked the second 500-year flood in the state in 1 year. Objective: The aim of this study was to identify private well user needs in the aftermath of the flood and to develop disaster planning and recovery recommendations for flood-prone well-reliant communities. Design: A descriptive cross-sectional study was conducted to collect information from a convenience sample of flood-impacted well users via surveys and water sampling kits, which were distributed to well users 9 to 11 weeks after floodwaters receded (n = 106). Setting: Surveys and kits were distributed at roadside flood response and recovery stations set up by local churches in French Settlement, Livingston Parish, Louisiana, an area at the epicenter of the flood-impacted area. Participants: Subjects were included if they self-reported having a flood-impacted well. Main Outcome Measures: Surveys collected information to characterize knowledge gaps, risk perceptions, flood impacts, resource accessibility, and well maintenance barriers. Well water tests evaluated total coliform and Escherichia coli . Results: Among those in low-risk flood zones (n = 22), 27% were in areas designated as having flooded. Among flood-impacted wells that were shock chlorinated after the flood (n = 16), 31.3% tested positive for total coliform and 12.5% for E coli . Only 26% of respondents received well-related information after the disaster. Conclusions: Results highlight critical needs for disaster planning and well user education in flood-prone areas, changes to flood risk maps, and concerns with the efficacy of disinfection strategies. Information and resources needs for flood-impacted well users are presented and recommendations on how to improve flood preparedness and recovery are made. Abstract : Supplemental Digital Content is Available in the Text.